Heteroatomic deltahedral clusters: synthesis and structures of closo-[Bi3Ni(4)(CO)6]3-, closo-[Bi4Ni4(CO)6]2-, the open cluster [Bi3Ni6(CO)9]3-, and the intermetalloid closo-[Nix@[Bi6Ni6(CO)8)]4-. - Goicoechea, J; Hull, M; Sevov, S (2007)
Reactions of ethylenediamine solutions of K4Bi5 with Ni(PPh3)2(CO)2 yielded four novel hetero-atomic Bi/Ni deltahedral clusters. Three of them, the 7-atom pentagonal bipyramidal [Bi3Ni4(CO)6]3-, the 8-atom dodecahedral [Bi4Ni4(CO)6]2-, and the Ni-centered or empty 12-atom icosahedral [Nix@[Bi6Ni6(CO)8]4-, are closo-species according to both electron count and shape. The centered icosahedral cluster resembles packing in intermetallic compounds and belongs to the emerging class of intermetalloid clusters. The shape of the fourth cluster, [Bi3Ni6(CO)9]3-, can be derived from the icosahedral Ni-centered [Ni@[Bi6Ni6(CO)8]4- by removal of three Bi- and one Ni-atoms of two neighboring triangular faces. The clusters were structurally characterized by single-crystal X-ray diffraction in compounds with potassium cations sequestered by 2,2,2-crypt or 18-crown-6 ether. They were also characterized in solution by electrospray mass spectrometry.